Kontribusi Neraca Perdagangan Komoditas Jagung Terhadap PDB[ - Desti Agustia Putri; Syarif Imam Hidayat Syarif; Dona Wahyuning Laily (Universitas Medan Area, 2026)
The purpose of this study is to analyze the contribution of the corn commodity trade balance to GDP. This study uses quantitative research using secondary data from the Central Statistics Agency (BPS), Trade Map, and UN Comtrade. The variables used in this study are the corn commodity trade balance and Gross Domestic Product (GDP) in Indonesia. The corn commodity data used is HS (100590) corn (maize) other than corn seeds, for the period 1989-2024. It was analyzed using the Vector Error Correction Model (VECM) method with Eviews 12 software. The results of this study indicate that the corn commodity trade balance and GDP have no short-term and long-term effects, even though they are cointegrated. However, the Error Correction Term (ECT) coefficient has a negative and significant value, even though its contribution is indirect. In the short term, the contribution of the corn trade balance to GDP was only 1.474892%. Meanwhile, in the long term, the contribution of the corn trade balance to GDP reached 94.16855%. Keywords: Trade Balance; Corn; GDP; Vector Error Correction Model (VECM)